Beyond the Rocks Based on a Novel by Elinor Glyn - Vrienten, Henny (Filmmuseum, 2005)
Theodora is the wayward daughter of retired Captain Fitzgerald. Trying to get by on a meager pension and caring for his two other spinster daughters, the entire Fitzgerald family is in dire straights. They want Theodora to marry a fat, elderly millionaire named Josiah Brown. Recently, though, Theodora has met Lord Hector Bracondale, a playboy cad whose rowdy reputation precedes him. Naturally, she ends up with Mr. Brown to save the family. Finding herself traveling in higher social circles, Theodora is constantly running into Lord Bracondale. He rescues her from a near fatal fall in the Alps and makes sure to have her invited to a swanky countryside estate. Though she feels deeply for the nobleman, she cannot break her marriage vow ... Though it marked the one and only time silent film superstars Rudolph Valentino and Gloria Swanson appeared together onscreen, there is more of note regarding the old-fashioned melodramatic mastery of "Beyond the Rocks" than this one-off pairing. For decades it was considered lost, a mere few seconds of footage remaining from the nearly 90-minute movie. When a print finally turned up in a private collection in 2000, it was considered something of a cinematic miracle ... While hokey and formulaic, "Beyond the Rocks" rejects the notion that all silent film was hysterical, overdone, and cartoonish. Both Valentino and Swanson give subtle, shaded performances, and Wood keeps the screen alive with electrifying compositions, fantastic narrative control, and some incredibly stunning visuals. [www.dvdverdict.com]